Assessing the volume of money laundering in Iran’s economy using the capital flight approach - Mahsa Saeedi Goraghani; Kazem Yavari (International Journal of Business and Development Studies)
Money laundering refers to the concealment of the illegal origin of proceeds obtained from criminal activities, making it appear as if they stem from legal sources. This phenomenon has numerous negative impacts on various economic and social spheres; thus, the countries` authorities - alongside international bodies - have sought to combat it by enacting the necessary laws and regulations and enforcing them. This collaboration occurs to prevent the establishment of a free zone for money laundering and ensures that the efficiency of enforcing these regulations is not disrupted. Iran, due to being in the financial Action Task Force (FATF) blacklist, is considered a free zone from this perspective. This makes the research on evaluating money laundering methods applicable to this country and also makes selecting suitable methods significant and appealing. Therefore, this study utilized the findings of the study by Hendriyetty and Grewal (2017) and, considering the information limitations in Iran, employed a combination method using capital flight approach as an index for measuring money laundering. The results of the research indicate that over a 28-year period, from 1995 to 2022, approximately 553 billion dollars have been laundered in Iran, averaging about 20 billion dollars annually. The highest amount of money laundering in Iran occurred in 2011, during which nearly 55 billion dollars was laundered in the country. Additionally, the observations show the lowest amount of money laundering at around 4.8 billion dollars in 2001.